Fresh Initiative_Sociodemographic and dietary intake data of high school student in the communes of Boukoumbe and Natitingou, northern Benin - Koukou, Elie; Bodjrenou, Fifali Sam Ulrich; Termote, Celine; Amoussa Hounkpatin, Waliou; Houndolo, Melina Maureen (2024)
This study aims to access food environment of high school students and the policies to improve fruits and vegetable’s availability in Northern Bénin. This study covered the communes of Boukoumbe and Natitingou.